Prevention of cervical cancer in South Africa : opportunities and challenges - Moodley, Jennifer Rose (Department of Public Health and Family Medicine, 2015)
This thesis examines the challenges to and opportunities for comprehensive (primary and secondary) prevention of cervical cancer in South Africa (SA), a middle-income country.